A Comparative Transcriptomic Analysis of miRNAs and Their Target Genes During the Formation of Melanin in Apis mellifera - Xiangjie Zhu; Yuanmingyue Tian; Mingjie Cao; Chenyu Zhu; Jiaqi Shang; Jiaqi Sun; Yiming Liu; Bingfeng Zhou; Shujing Zhou; Xinjian Xu (Agriculture)
Melanin is an important component of the body color of honeybees, and its formation changes with the age of a capped brood of bees. However, up to now, the regulatory mechanism of melanin formation in honeybees remains unclear. To analyze the differential expression profile of microRNAs (miRNAs) in worker bees of Apis mellifera and to reveal the regulatory roles of differentially expressed miRNAs (DEmiRNAs) and mRNAs in the formation process of melanin during the capped brood stage, we used sRNA-seq technology and related software to analyze samples from four key developmental stages during the capped brood stage, when body color develops in Apis mellifera, namely, mature larvae (L0), pre-pupae (PP3), early pupae (P6) and mid-pupae (P9). A total of 1291 miRNAs were identified by bioinformatics. Three comparison groups were analyzed: L0 vs. PP3, PP3 vs. P6, and P6 vs. P9. A total of 171, 94, and 19 DEmiRNAs were identified in these groups, respectively, which regulate 1481, 690, and 182 differentially expressed target mRNAs (target DEmRNAs). The functional analysis of target DEmRNAs indicated that DEmiRNAs might regulate the formation of capped brood melanin in honeybees by activating expression changes in key genes in signaling pathways, such as the Wnt signaling pathway, melanogenesis, and the Toll and Imd signaling pathway, through activating miR-315-x, miR-8, ple, yellow family genes, wnt1, etc. Our research provides a theoretical basis for future analysis of the regulatory role of miRNAs in the formation of melanin in honeybees.